Ileoileal Intussusception Secondary to Meckel's Diverticulum: A Case Report - Sylvia Noviani Saing; Eriska Geriana Permatasari Saing (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The most frequently documented aetiology of Meckel's related obstructions is volvulus or intussusception of the small bowel with the presence of Meckel's diverticulum as the lead point. This study presents a case of small bowel obstruction caused by intussusception due to Meckel's diverticulum, which led to an obstruction of the small intestine. Case presentation: A 17-year-old male patient visited the hospital's emergency room complaining of worsening abdomen pain for two days. It was associated with abdominal distention, fever, nausea, and vomiting. There was no roving's sign or psoas sign and no rebound tenderness. There is no history of gastrointestinal cancer in his family or previous abdominal surgery. The white blood cell count was 18,400 c/mm, and the electrolytes, liver function tests (LFTs), and urinalysis were all within normal ranges. Ultrasonography imaging of right lower quadrant (RLQ): thickening tubular structure with target sign view and enteric intussusception with the possibility of appendix component. Conclusion: A 17-year-old male went to the emergency room complaining of acute abdominal pain and was diagnosed with ileoileal intussusception intraoperatively.